Mismatched and misaligned: responsibility narratives in American research labs for synthetic biotechnologies - Maya Hey (Journal of Responsible Innovation)
This article examines what responsibility means in the context of synthetic biotechnologies, based on academic researchers in the American west who are using/developing synthetic biology, engineering biology, and synthetic genomics. Advancements in technical capacity are ushering in imminent/current possibilities of creating whole genomes/organisms from scratch, yet extant narratives about ‘responsibility’ have neither been fleshed out, nor compared against normative frameworks (such as ELSI and its critiques). Through empirical data collection (e.g. discourse analysis), this paper examines interviews with biotechnologists (N = 16) to analyze responsibility narratives on the ground, which include: being responsible towards grand challenges, national values, and research relations involving other beings in the lab, both human and more-than-human. The analyses presented here offer feminist and multispecies critiques for studying the relational webs of responsible (response-able) research and concludes with a discussion about the mismatch between how responsibilities are narrativized across different actors within academic research institutions.